DAYA SAING PENGOLAHAN KOPI BUBUK DI KOTA BENGKULU - Romdhon, M. Mustopa (Jurnal AGRISEP, 2006)
The Coffee has economic prospective commodity for Bengkulu PDRB since its be regional key commodity. But limitation of capital, production technology, and market information have reduced their competitiveness. The research aims to elaborate the advantage of coffee processing at Bengkulu Municipal. Processing coffe industry at Bengkulu city faced to finacial, production technology and market information burdens,generally. Its later lead to reduced the industries competitive advantage. Commonly, the compettitve advantage was quite better, its showed by revenue-cost ratio about 1,26. But uncertainty condition such scarcity of fuel, raw materials, and under capacity of production then accompanied by rose of fuel price have brought the industries to worse condition. Anything have to be done by government as soon as possible under private assistance along with university.